Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1308/rcsann.2020.7079
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laparoscopy on emergency surgery for adhesional small bowel obstruction: prospective single centre cohort study

Abstract: Introduction Laparoscopic adhesiolysis is increasingly being used to treat adhesional small bowel obstruction (ASBO) as it has been associated with reduced postoperative length of stay (LOS) and faster recovery. However, concerns regarding limited working space, iatrogenic bowel injury and failure to relieve the obstruction have limited its uptake. This study reports our centre’s experience of adopting laparoscopy as the standard operative approach. Methods A single-centre prospective cohort study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The LaCeS randomised feasibility study demonstrated that emergency laparoscopic colorectal surgery is safe but was only designed to inform a future trial [30]. Other registry-based studies investigating adhesiolysis, perforated peptic ulcer repairs and colorectal resections have reported improved outcomes with laparoscopy but are restricted by their observational nature [31][32][33]. It does make intuitive sense that the reduced post-operative pain and physiological burden conferred by minimally invasive surgery could translate to a survival advantage, in the high-risk patients This study is of course limited by its observational nature and the potential for selection bias that comes with it.…”
Section: Discussionmentioning
confidence: 99%
“…The LaCeS randomised feasibility study demonstrated that emergency laparoscopic colorectal surgery is safe but was only designed to inform a future trial [30]. Other registry-based studies investigating adhesiolysis, perforated peptic ulcer repairs and colorectal resections have reported improved outcomes with laparoscopy but are restricted by their observational nature [31][32][33]. It does make intuitive sense that the reduced post-operative pain and physiological burden conferred by minimally invasive surgery could translate to a survival advantage, in the high-risk patients This study is of course limited by its observational nature and the potential for selection bias that comes with it.…”
Section: Discussionmentioning
confidence: 99%
“…Papers have shown patients undergoing laparoscopic vs open approach for adhesional SBO and perforated peptic ulcers have significantly better outcomes, with lower complication rates and mortality. 22,23 An analysis of the NELA database in 2022 showed riskadjusted mortality for emergency bowel surgery is lower for laparoscopy compared with open surgery, and that the P-POSSUM and NELA scores overpredict mortality for laparoscopic emergency abdominal operations. 24 Based on our results, as well as the current literature available, it is acceptable to conclude that laparoscopy is associated with improved perioperative outcome in the acute abdomen and it would be considered reasonable to attempt a minimally invasive approach, where clinically feasible, for emergency laparotomy patients.…”
Section: Postoperative Outcomesmentioning
confidence: 99%